(untitled) (Global Journal of Human-Social Science, 2023)
This article studies Cuba s 30 years of innovation and socialist goals After the Introduction and before the Conclusion the primary content of the article is divided into three parts The first part looks at the general situation of Cuba s reform process over the past 30 years 1993-2023 The second part identifies analyzes and demonstrates typical factors that directly impact the pace of development and expansion of cooperation in Cuba The third part reviews and evaluates Cuba s prospects orientation and development potential